3, 5, 6-trichloro-2-pyridinol intensifies the effect of chlorpyrifos on the paracrine function of Sertoli cells by preventing binding of testosterone and the androgen receptor. (August 2021) - Gao, Haina; Li, Jinwang; Zhao, Guoping; Li, Yixuan
Graphical abstract: Highlights: CPF damage paracrine function of Sertoli cells in vivo and in vitro . CPF damage paracrine function through inhibit testosterone bind to androgen receptor. Only TCP structure intensified CPF induced inhibition effect on testosterone bind to androgen receptor. Abstract: 3, 5, 6-Trichloro-2-pyridinol (TCP ) is an important biomarker and one of the final metabolites of chlorpyrifos (CPF ). TCP inhibits secretion of sex hormones. Similar to CPF, TCP can bind to sex steroid hormone receptors and decrease the secretion of sex hormones. However, little attention has been paid to the ability of TCP and CPF to interfere with androgen receptor (AR ) in Sertoli cells. This study aimed to explain how TCP promotes the inhibitory effect of CPF on the paracrine function of Sertoli cells. Western blotting indicated that after 20 weeks of exposure, expression of AR in testes was significantly reduced by CPF. An in vitro assay measured the cytotoxicity of CPF, TCP and diethylphosphate (DEP ) on viability of Sertoli cells by Cell Counting Kit-8. CPF cytotoxicity was greater than that of TCP, and TCP cytotoxicity was greater than that of DEP at concentrations of 1000 μmol/L. Western blotting indicated that TCP and CPF both decreased expression of AR and cAMP-response element binding protein phosphorylation, while DEP had no effect in Sertoli cells, which are important in regulating paracrine function of Sertoli cells. The fluorescence measurements and docking studies revealed that testosterone, CPF and TCP showed four types of intermolecular interactions with AR, highlighting alkyl bonds with some of the same amino acids. Compared with testosterone, CPF and TCP also showed significant synergistic interaction with AR. CPF interacted with more amino acids and interaction energy than TCP did. This research elucidates TCP in the antiandrogenic effect of CPF on the paracrine function and suggests that TCP or chemicals with a trichloropyridine structure must be considered during reproductive toxicity assessment of potential environmental pollutants.